Optimizing an Ultisol of marginal land for soybean cultivation through inorganic fertilizer substitution with Tithonia compost and biochar ameliorant - Lestari, Ardiyaningsih Puji; Zulkarnain; Adriani; Mapegau; Nusifera, Sosiawan; Martino , Dede (Brawijaya University, 2024)
Soybean has a strategic role as a food commodity in Jambi, Indonesia, but until now, it has still not been self-sufficient. There is still an opportunity to increase soybean productivity in Jambi by 35-49.6% by optimizing the use of marginal, dominated by Ultisol, which has low inherent soil fertility. One of the efforts that can be made to improve soil fertility for cultivating soybean plants in Jambi is to utilize compost and biochar as soil ameliorants to substitute for inorganic fertilizer. This study aimed to assess the effect of compost and biochar ameliorant as substitutes for inorganic fertilizer on the growth and yield of soybean plants grown on an Ultisol of Jambi. The experiment was arranged in a simple randomized block design with the combination of the percentage of inorganic fertilizer with compost and biochar ameliorant (100+0, 75+25, 50+50, 25+75, and 0+100) as the treatment factors. The observed variables were plant height, number of branches, plant nitrogen content, rate of symbiotically fixed nitrogen, weight of 100 seeds, and yield. The results showed that providing compost and biochar ameliorants can replace the role of inorganic fertilizer, and providing 100% compost and biochar ameliorant and a combination of 25% inorganic fertilizer and 75% compost biochar ameliorant can provide the highest growth and yield in soybean plants planted in Ultisol dry land.